Acylation of Hexaphenylbenzene for the Synthesis of [5]Cumulenes. Issue 17 (28th January 2022) - Johnson, Matthew A.; Martin, Max M.; Cocq, Kévin; Jux, Norbert; Ferguson, Michael J.; Tykwinski, Rik R.
Abstract: The Friedel‐Crafts acylation of hexaphenylbenzene is reported, and the reaction favorably provides the monoacylated products 1 a and 1 b . The resulting ketones 1 a and 1 b are used as precursors for the formation of [5]cumulenes, including 6 b in which the sterically demanding HPB moiety affords a diethynyl[5]cumulene that features significant stability (persistence) versus the analog 6 c which lacks the HPB endgroups. The unsymmetrical substitution pattern of the two most soluble derivatives 6 b and 6 c, allows for estimation of rotational barriers for diethynyl[5]cumulenes via VT NMR studies of cis‐trans isomerization. For both molecules, the barrier to rotation is ca. 15 kcal mol −1, which is attenuated in comparison to other [5]cumulenes due to the presence of the ethynyl endgroups. Abstract : Hexaphenylbenzene is appended to [5]cumulenes, a marriage of sp‐ and sp 2 ‐carbon building blocks for synthetic allotropes.